Alfabeto fotografico - Tulli, Vittorio (Cnr Edizioni, 2023)
The contribution presents the photographic alphabet made up of 21 photographs taken by Vittorio Tulli in Ny-Ålesund with commentary and captions by anthropologist Paola Atzeni. The alphabet is part of the traveling exhibition “4,404 km: Soil and Subsoil”, which has the metaphor of the voyage of discovery as a common thread. Beginning with a glimpse into the depths and darkness, then moving towards the horizons of knowledge, represented by the North Pole, the exhibition explores the possibilities and limits of knowledge.